2000
DOI: 10.1046/j.1462-5822.2000.00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Yersinia enterocolitica across reconstituted intestinal epithelial monolayers is triggered by Yersinia invasin binding to beta1 integrins apically expressed on M-like cells

Abstract: SummaryYersinia enterocolitica cross the intestinal epithelium via translocation through M cells, which are located in the follicle-associated epithelium (FAE) of Peyer's patches (PP). To investigate the molecular basis of this process, studies were performed using a recently developed in vitro model, in which the enterocyte-like cell line Caco-2 and PP lymphocytes are co-cultured in order to establish FAE-like structures including M cells. Here, we demonstrate that Y. enterocolitica does not adhere significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
86
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 58 publications
2
86
2
1
Order By: Relevance
“…Mechanisms of uptake and transport were studied by microscopy and by pharmacological inhibition studies in human FAE tissue, as well as in the in vitro lymphocyte-epithelial cell coculture model of human FAE initially described by Kerneís et al, 11 and subsequently used by several groups to study FAE and M-cell function. [12][13][14][15][16][17][18] Our findings show that human ileal FAE is not only structurally, but also functionally distinct from regular VE, with enhanced transport of antigens and bacteria into the underlying lymphoid tissue.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…Mechanisms of uptake and transport were studied by microscopy and by pharmacological inhibition studies in human FAE tissue, as well as in the in vitro lymphocyte-epithelial cell coculture model of human FAE initially described by Kerneís et al, 11 and subsequently used by several groups to study FAE and M-cell function. [12][13][14][15][16][17][18] Our findings show that human ileal FAE is not only structurally, but also functionally distinct from regular VE, with enhanced transport of antigens and bacteria into the underlying lymphoid tissue.…”
mentioning
confidence: 63%
“…In a paper by Kerneís et al 11 it was shown that coculture of Peyer's patch lymphocytes and intestinal epithelial cells may trigger conversion of the epithelial cells to M cells. This model and variants of it have been used to study M-cell function, [12][13][14][15][16][17] and by using our previously established modification 18 of the original model, mechanisms of antigen and bacterial uptake could be studied. Briefly, intestinal epithelial Caco-2 cells were grown on Matrigelt (Becton Dickinson, USA) coated polycarbonate filters (Costar, Baedvenhorp, NL, USA) with a mean pore size of 3.0 mm.…”
Section: Coculture Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the number of intracellular bacteria, a gentamicin protection assays was performed as described earlier. 28 Briefly, cultures were washed with PBS and incubated for 1 h in the presence of gentamicin (100 mg/ml) to kill remaining extracellular bacteria. Cells were lysed with 1% Triton X-100 in PBS, and intracellular viable bacteria assessed by plating serial 10-fold dilutions on plates with kanamycin (50 mg/ml) and ampicillin (100 mg/ml).…”
Section: Bacterial Incubationsmentioning
confidence: 99%
“…Together, these two proteins mediate initial adhesion, uptake and translocation of Yersinia across the intestinal epithelium. 26,27 Invasin is known to exert its effect via a high-affinity interaction with b1-integrin, which is expressed on the luminal surface of M-cells (epithelial cell type specialized in antigen and bacterial uptake), 28,29 but only on the basolateral aspect of villus epithelial cells.…”
mentioning
confidence: 99%